Implementasi Kebijakan Sistem Informasi Manajemen (SIM-Siluhtan) dalam Pelaksanaan Program Dekonsentrasi Penyuluhan Pertanian di Provinsi Kalimantan Utara - Yohanis Sallolo; Sofjan Aripin; Djoko Raharjo (Universitas Terbuka, 2022)
Abstract SIM-Siluhtan is website-based information system used as a media for reporting the implementing of the deconcentration program of agriculture extention (PDPP) in North Kalimantan Province since 2017. The research wasconducted in three districts, Bulungan, Nunukan, Malinau using data from 2018-2019 to decribe and analyze SIM-Siluhtan implementation policies in the implementing at the deconcentration program activities, as well as the factors that support and hinder the implementation and also the effort made in implementing. This study uses a descriptive qualitative method based on Edward III’s theory to describe and explore the fact that the implementation of public policy can be effective, depending on the four factors thae influence its success, namely communication, resources, disposition, and bureaucratic structure. The results showed that overall the stage of the SIM-Siluhtan implementation process with a span of control involving the provincial, distric and subdistrict /BPP levels were successful in achieving the performance target and by prioritizing the principles of transparency and publication in the policy implementation which is intensive with support of human resource capabilities of the implementer in carrying out their duties and aothorities so that collaboration and communication are build out which supported by publication of media communication, namely Facebook, WhatsApp, as well as adequate budged support and infrastructure, althouh not maximized due to technical contraints in the field. Keywords : SIM-Siluhtan Implementation, Communication, Resource, Disposition, Bureaucratic Structure.